La geografia delle piattaforme digitali Mappe, spazi e dati dell'intermediazione digitale - Romano, Antonello (Strumenti per la didattica e la ricerca, 2022)
The Atlas aims to offer an empirically-situated view on the socio-spatial effects mediated by the digital platforms by adopting a critical and geographical data-centric approach. The objective is to provide a practical understanding of the consequences of the digital platform's pervasiveness and its differential impacts on space and places: the (uneven) geography of the digital platforms. By employing maps, graphs and alternative cartographic representations we intend to make those socio-spatial relationships and impacts immediately visible and more understandable. The Atlas, therefore, offers food for critical reflection on the socio-spatial inequalities amplified by the platforms and on the potential use (eg. public value) of the platform's spatial Big Data. The work combines Spatial Analysis, Social Network Analysis and Data Viz adding a further dimension, the spatial one, to the debate on the platform society.